2021
DOI: 10.3889/oamjms.2021.6388
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Stroke in Simultaneous Cardio Cerebral Infarction: A New Term for Cardiologist

Abstract: We report an uncommon case of simultaneous cardio-cerebral infarction, due to Inferior – right ventricle ST Segment Elevation Myocardial Infarction (STEMI) with acute ischemic stroke. Incidence of cardio cerebral infarction is exceptionally rare, with an incidence rate as low as 0.009%. Hemodynamic compromise in patients with acute myocardial infarction may result in the cerebral blood flow reduction that cause hemodynamic stroke. Due to the rarity of this condition, there were no recommended therapeutics stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The fact that symptoms develop following movements that may conceivably cause cerebral hypoperfusion, such as getting out of bed or a chair or hyperextending the neck, is a practically universal clinical signal. In patients with severe carotid stenosis, postural change may momentarily impair brain perfusion [7] . The majority of these assaults, as was the case with our patient, happened when she stood up from a laying or sitting posture.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that symptoms develop following movements that may conceivably cause cerebral hypoperfusion, such as getting out of bed or a chair or hyperextending the neck, is a practically universal clinical signal. In patients with severe carotid stenosis, postural change may momentarily impair brain perfusion [7] . The majority of these assaults, as was the case with our patient, happened when she stood up from a laying or sitting posture.…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic monitoring, including the examination of physical aspects of blood circulation, heart function, and peripheral vascular physiological characteristics, aims to detect and identify physiological abnormalities early [11] . According to Yusuf et al (2021), parameters often used to assess a patient's hemodynamic status include Mean Arterial Pressure (MAP), which is an assessment of hemodynamic status based on blood pressure and Heart Rate through manual measurement on the radial artery within one minute [12] . Previous studies have shown the correlation between hemodynamic status and stroke risk in hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…when the cause of hypertension cannot be identified (idiopathic) and mostly is a complex interaction between genetics and environmental interactions. The classification of hypertension is divided into four categories, namely normal with systolic <120 mmHg and diastolic <80 mmHg, pre-hypertension systolic 120-139 mmHg and/or diastolic 80-89 mmHg, stage 1 hypertension with systolic 140-159 mmHg and/or diastolic 90-99, and grade 2 hypertension with systolic 160 mmHg and/or 100 mmHg (Harris, Kurniawan, et al, 2018;Yusuf et al, 2021).…”
Section: Introductionmentioning
confidence: 99%